ASEAN ATTITUDES TOWARD PATENT PROTECTION OF THE COVID-19 VACCINE VERSUS HUMANITARIAN INTERESTS - Situmeang, Tomson; Murniarti, Erni (Jurnal Hukum dan Peradilan, 2021)
The global pandemic of the Covid-19 outbreak has caused problems in various aspects of life. Several countries have invented or made the Covid-19 vaccine. However, there are still many countries that have not been able to find or make the Covid-19 vaccine, including ASEAN countries. This raises questions that are the topic of discussion in this article, namely about ASEAN's attitude towards 2 different interests between patent protection for the Covid-19 vaccine and humanitarian interests in overcoming the Covid-19 outbreak. Does Patent protection take priority or humanitarian interest take precedence? To discuss this topic, the authors use normative legal research methods based on secondary data or bibliography. The topic was discussed by comparing various legal provisions, both national and international, in order to obtain the main findings stating that patent protection also prioritizes humanitarian interests